A Review on Interesting Properties of Chicken Feather as Low-Cost Adsorbent - Moon, Wei Chek (International Journal of Integrated Engineering, 2019)
Adsorption process has been used widely in the treatments related to environmental issues due to its modestness and ease of operation. Through the years, the development of low-cost absorbents has been given much attention in the adsorption process. The applications of chicken feather, a byproduct in poultry farming on wastewater treatment are boon for the worldwide researchers. In this review paper, the possible mechanism of adsorption, the adsorption isotherms and the factors affecting the adsorption process are first discussed. Next, this paper provides a review on the potential low-cost adsorbent of chicken feather: its composition, morphological structure and properties. This paper also describes the preparation of chicken feather as an adsorbent with different activation methods. The unique morphological structure of chicken feather enhances its interesting properties for several types of applications purposes. Lastly, the applications of chicken feather proved by the past studies are presented in this paper.